Implementasi Manajemen dan Digitalisasi Perpustakaan di Lembaga Pendidikan SMAN 13 Surabaya - Cahyani, Davina; Adni, Shofy; Kartika, Engga; Salsabila, Salma; Anggraini, Della; Rahmawati, Febiana; Amelia, Elsa; Fitria, Rezki (Indonesian Journal Publisher, 2025)
This study discusses the implementation of library management and digitalization at SMAN 13 Surabaya in response to the advancement of information technology in education. The library’s digitalization is realized through the application of online cataloging (OPAC), online book borrowing and returning services, and the development of an e-book collection accessible exclusively to students. Additionally, the library organizes literacy programs such as